2021
DOI: 10.1186/s12871-021-01402-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative lung-protective ventilation on clinical outcomes in patients with traumatic brain injury: a randomized controlled trial

Abstract: Background Secondary lung injury is the most common non-neurological complication after traumatic brain injury (TBI). Lung-protective ventilation (LPV) has been proven to improve perioperative oxygenation and lung compliance in some critical patients. This study aimed to investigate whether intraoperative LPV could improve respiratory function and prevent postoperative complications in emergency TBI patients. Methods Ninety TBI patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… Robba et al [ 80 ] Prospective observational study 15 patients with ABI (6 SAH patients, 6 TBI patients, 3 ICH patients) In patients with ABI, C RS , lower MAP, and lung recruitment are associated with ICP rise following incremental levels of PEEP (two levels of PEEP were tested: 5 and 15 cmH 2 O); however, none of those factors was able to predict at baseline the effect of PEEP over ICP. Jiang et al [ 63 ] Randomized controlled trial 90 TBI patients who underwent emergency intracranial hematoma evacuation ONSD (used as ICP change detector method) does not change between patients assisted with traditional MV (V T 10 mL/kg+ 0 cmH 2 O PEEP) and small V T (8 mL/kg) + 5 cmH 2 O PEEP. During a single RM ONSD transiently increased but returned to baseline in 5–10 min, suggesting that RMs could elevate ICP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Robba et al [ 80 ] Prospective observational study 15 patients with ABI (6 SAH patients, 6 TBI patients, 3 ICH patients) In patients with ABI, C RS , lower MAP, and lung recruitment are associated with ICP rise following incremental levels of PEEP (two levels of PEEP were tested: 5 and 15 cmH 2 O); however, none of those factors was able to predict at baseline the effect of PEEP over ICP. Jiang et al [ 63 ] Randomized controlled trial 90 TBI patients who underwent emergency intracranial hematoma evacuation ONSD (used as ICP change detector method) does not change between patients assisted with traditional MV (V T 10 mL/kg+ 0 cmH 2 O PEEP) and small V T (8 mL/kg) + 5 cmH 2 O PEEP. During a single RM ONSD transiently increased but returned to baseline in 5–10 min, suggesting that RMs could elevate ICP.…”
Section: Resultsmentioning
confidence: 99%
“…Optic nerve sheath diameter (ONSD) is a bedside non-invasive technique for monitoring changes in ICP. Jiang et al [ 63 ] measured ONSD in TBI patients managed with two different approaches: traditional MV (V T 10 mL/kg + 0 cmH 2 O PEEP) and small V T (8 mL/kg) + 5 cmH 2 O PEEP; no significant differences were seen in ONDS and consequently in the MV approach regarding ICP. During a single recruitment maneuver (RM) (maintain an airway pressure of 30 cmH 2 O for 30 s), the ONSD increased and returned to baseline after 5–10 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis reported a significant increase in serum UCH-L1 levels in patients with traumatic brain injury compared to controls [52]. GFAP and UCH-L1 have been used as biomarkers of traumatic brain injury [53]. Studies have reported an increase in blood GFAP levels in neuroinflammation with potential clinical applications [54].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 9 The calculation of the best PEEP is still a challenge, and several strategies were studied for titrating the best level of PEEP. 10 …”
mentioning
confidence: 99%